Kingdom of Swaziland : Staff Monitored Program-Staff Report; Staff Supplement. (IMF Staff Country Reports; Country Report, 2011)
The Swaziland economy continues to suffer from the global economic crisis and an overvalued real exchange rate. The fiscal crisis is starting to affect external stability. Notwithstanding the fiscal crisis, banks continue to remain well capitalized and profitable. The 2011-12 budget promises to make significant progress in fiscal adjustment while safeguarding priority expenditures. The government is taking ambitious measures to cut the wage bill in FY2011-12. Improvements in revenue administration by the Swaziland Revenue Authority (SRA) will strengthen revenue collections.